JD Edwards EnterpriseOne 8.9 High Availability and Storage for the IBM eServer pSeries Client - Redbooks, IBM (I B M, 2005)
As companies depend more and more on their enterprise software for daily operations, they require highly available systems. JD Edwards EnterpriseOne has long enabled their software with the IBM High Availability Cluster Multi-Processing (HACMP) product for high availability.This IBM Redbooks publication describes the IBM HACMP/Enhanced Scalability (HACMP/ES) Version 4.5 solution to certify JD Edwards EnterpriseOne 8.9 in an IBM AIX high availability environment. This book also describes HACMP/ES Version 5.1. It explains how to install and tune HACMP/ES, as well as reviews the setup steps to enable JD Edwards EnterpriseOne for HACMP/ES.While writing this book, we conducted tests to simulate that the failures and observations made to ensure that the high availability environment performed properly. The results of these tests are also documented.This book highlights and explains those characteristics that are specific to JD Edwards EnterpriseOne. It contains significant window examples and worksheets to help facilitate an easy step-by-step installation process. It does not replace the extensive installation and administration documentation that is already available for HACMP/ES.